IEO Annual Report 2005-06. - International Monetary Fund. Independent Evaluation Office (Washington, D.C. : International Monetary Fund, 2007)
The IMF's surveillance framework encompasses a new focus on multilateral issues, and especially the spillovers from one economy onto others. This third Annual Report of the Independent Evaluation Office describes ongoing and recently completed evaluations and discusses additions to IEO's work plan. General lessons pertaining to IMF surveillance emerging from recent evaluations are highlighted and discussed, namely the need for better integration of financial and macroeconomic factors as well as bilateral and multilateral policy analysis and policy prescriptions. The findings of an External Evaluation Panel charged with assessing the work of the IEO are also covered.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet